Bacterial growth dynamics and corresponding metabolite levels in the extraction area of an Austrian sugar beet factory using antimicrobial treatment. (11th February 2020) - Kohout, Cordula K; Ukowitz, Christina; Reiter, Dominik; Zitz, Ulrike; Moder, Karl; Emerstorfer, Florian; Hein, Walter; Kneifel, Wolfgang; Domig, Konrad J
Abstract: BACKGROUND: During the manufacture of sucrose from sugar beet, different microorganisms originating from the plant material as well as from the soil enter the process. Due to the formation of polysaccharide‐based slimes, these contaminants may induce several adverse effects such as filtration problems during juice purification. Certain microorganisms also metabolize sucrose, leading to product losses with financial consequences. To better understand and to prevent these negative effects, the aim of the study was to investigate the evolution of relevant bacterial groups, including their metabolites appearing during the extraction process. For this purpose, one production cycle was monitored to identify the major contamination steps and to clarify how they relate to the processing conditions. Traditionally, different antimicrobial agents such as formaldehyde, sulfur dioxide, hypochlorous acid, sodium hypochlorite, and chlorine dioxide have been added to inhibit microbial growth. In the present study, a rosin‐based product derived from pine trees was applied as an alternative to those substances. RESULTS: Press water, raw juice, and mid‐tower juice were identified as being highly contaminated with bacteria, and processing conditions such as time, temperature and pH level significantly influenced bacterial levels and the corresponding metabolites. Among the contaminants identified, lactic acid bacteria, and mesophilic and thermophilic aerobic bacteria played a dominant role, whereas lactic acid, acetic acid, butyric acid, and ethanol were identified as typical metabolites. CONCLUSION: Bacterial growth during production could be reduced by shock dosing of the rosin‐based material in the extraction area. © 2020 Society of Chemical Industry